Customers’ Switching Behavior In Banking In The Special Region Of Yogyakarta Province Indonesia - Rofiul Wahyudi (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2017)
This study aims to provide influence on the customer‟s switching behavior in islamic banking in the special region of Yogyakarta Province, Indonesia. Design/Methodology/Approach Multiple Regression were used to examine the influence of attitude towards switching, subjective norm, financial bonding, social bonding, structural bonding toward switching customers‟ behavior. Findings The result responses the variable of the attitude towards and subjective norm and financial bonding, social bonding, structural bonding significant to the switching intention to a conventional bank. Findings indicated it interaction between switching intention and customer satisfaction for customers‟ switching behavior. Research implication and recommendations Perhaps the most important finding of this research is those banking players particularly improvement customer satisfaction and identifying most factors driving intention to customers‟ switching.